2017
DOI: 10.22159/ijpps.2017v9i4.17196
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Treatment Pattern and Outcomes of Poisoning Cases in a Tertiary Care and Government District Hospital

Abstract: Objective: Poisoning is a major prevalent problem, with thousands of deaths occurring every year, mainly in developing countries. The present study sought to identify the treatment pattern and outcomes of poisoning cases admitted to Basaveshwara Medical College and Hospital and Research Centre (BMCH and RC) and Government District Hospital and to determine the type of poison cases.Methods: This is a prospective observational study aimed to analyse the poisoning cases admitted to general medicine departments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
3
8
1
Order By: Relevance
“…The results from this study revealed that most of the cases reported to the emergency department for suicide attempt by self-poisoning were males, a finding that is contrary to the previous studies where female outnumbered male [6][7][8][9][10]. The male:female ratio was 1:0.86 and significant (p<0.01).…”
Section: Resultscontrasting
confidence: 82%
“…The results from this study revealed that most of the cases reported to the emergency department for suicide attempt by self-poisoning were males, a finding that is contrary to the previous studies where female outnumbered male [6][7][8][9][10]. The male:female ratio was 1:0.86 and significant (p<0.01).…”
Section: Resultscontrasting
confidence: 82%
“…Considering the result of this study, about 62.4% received first aid in which frequently administered techniques were gastric lavage along with activated charcoal and emesis irrespective of the nature and type of poison consistent with the results obtained in other studies [8,9]. People who did not receive first aid were probably brought to the hospital directly as they might have been geographically closer to the hospital and hence received appropriate treatment when compared to others.…”
Section: Discussionsupporting
confidence: 85%
“…Data from several national and international studies correlated with the present findings (Table 2), intentional poisoning is the main cause followed by accidental exposure (41.4%) which could have occurred due to consumption of poison mistaken as medicine, accidental spraying of chemical substances, and poisonous agents accidentally consumed by children [9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Organophosphorus poisoning was observed to be the most common method. 21-30 year olds were most prone to suicidal poisoning, ascribed to their perturbation concerning the future issues [24]. Similarly studies on heavy metal poisoning have been done, but such studies with cartap is lacking [25].…”
Section: Discussionmentioning
confidence: 99%